Toward a Typology of Office-based Buprenorphine Treatment Laws: Themes From a Review of State Laws. Issue 2 (18th March 2022) - Andraka-Christou, Barbara; Gordon, Adam J.; Bouskill, Kathryn; Smart, Rosanna; Randall-Kosich, Olivia; Golan, Matthew; Totaram, Rachel; Stein, Bradley D.
Abstract : Objectives: Buprenorphine is a gold standard treatment for opioid use disorder (OUD). Some US states have passed laws regulating office-based buprenorphine treatment (OBBT) for OUD, with requirements beyond those required in federal law. We sought to identify themes in state OBBT laws. Methods: Using search terms related to medications for OUD, we searched Westlaw software for state regulations and statutes in 51 US jurisdictions from 2005 to 2019. We identified and inductively analyzed OBBT laws for themes. Results: Since 2005, 10 states have passed a total of 181 OBBT laws. We identified the following themes: (1) provider credentials : state licensure for OBBT providers and continuing medical education requirements; (2) new patients : objective symptoms patients must have before receiving OBBT and exceptions for special populations; (3) educating patients : general informed consent requirements, and specific information to provide; (4) counseling : minimum counselor credentials, minimum counseling frequency, counseling alternatives; (5) patient monitoring : required prescription drug monitoring checks, frequency of drug screening, and responses to lost/stolen medications; (6) enhanced clinician monitoring : evidence-based treatment protocols, minimum clinician-patient contact frequency, health assessment requirements, and individualized treatment planning; and (7) patient safety : reconciling prescriptions, dosage limitations, naloxone coprescribing, tapering, and office closures. Conclusions: Some laws codify practices for which scientific consensus is lacking. Additionally, some OBBT laws resemble opioid treatment programs and pain management regulations. Results could serve as the basis for a typology of office-based treatment laws, which could facilitate empirical examination of policy impacts on treatment access and quality.